Microemulsion systems: from the design and architecture to the building of a new delivery system for multiple-route drug delivery - Egito, E. S.T.; Amaral-Machado, L.; Alencar, E. N.; Oliveira, A. G. [UNESP] (Springer Nature, 2020)
Abstract: Poorly soluble active pharmaceutical ingredients (APIs) create major problems in drug dosage form formulation resulting in significant delays in drug pharmaceutical screening, impairing the drug dosage form production. Aiming to minimize the use of excipients for increasing drug apparent solubility and, as a result, its bioavailability, exploration of innovative approaches is an earnest need. Microemulsion is an alternative drug delivery system that emerged as a valuable tool to achieve safe formulations for insoluble compounds and to improve their biopharmaceutical properties and pharmacokinetics. This review aims to present the state of the art of microemulsion systems, bringing an overview about their origin and how they can be properly produced and thoroughly characterized by different approaches. Furthermore, comments on regulatory issues regarding stability assessment and toxicity evaluation are discussed. The review concludes with a current opinion on microemulsion systems. The overall objective of this work was to describe all the potentialities of microemulsion systems as a drug carrier for therapeutic purposes, highlighting the unique features of this nanotechnological platform. Graphical abstract: [Figure not available: see fulltext.] Display Image
Keywords: Characterization; Marketed microemulsions; Nanomedicines; Regulatory aspects; Toxicity